ROLUL MALONDIALDEHIDEI ÎN EVALUAREA STATUSULUI OXIDATIV DIN DEPRECIERILE TERITORIULUI PARODONTAL - Toma Vasilica; Goriuc Ancuta; Cioloca Daniel; Irina Nechifor; Surdu Amelia; Maftei George; Foia Liliana; Filip Florina (Romanian Dental Association for Education, 2017)
Periodontal disease includes multiple and complex mechanisms that simultaneously encapsulate tissue destruction due to bacterial aggression, as well as exaggerated defense mechanisms of the host, which give rise to multiple contradictions in etiopathogenesis and management of the disease, the oxidative status playing a significant role. Objective. Considering the importance of the pro- and antioxidants balance within periodontal condition, we designed a clinical and biochemical study to estimate the levels of a biomarker of oxidative stress, malondialdehyde - MDA in the gingival fluid (GCF). Material and methods. The assessment has been performed in clinically healthy subjects (n=15) and periodontal patients with chronic periodontitis (n=16) versus aggressive periodontitis (n=11). Being a marker of lipid peroxidation, for all individuals malonyldialdehyde gingival fluid levels has been determined from the isolated supernatant, following centrifugation of crevicular fluid, through colorimetry techniques. Results. The separate MDA assessment displayed statistical significance of the values recorded in patients with chronic periodontitis compared to the group of healthy patients (p <0.0001), but also those with the aggressive form of disease (p <0.0001), without statistically significance between the two types of periodontal impairment. Conclusion. Despite the limitations imposed by the small size of the sample, the results obtained may be relevant, MDA being the only biomarker considered for determination. However, measuring other lipid peroxidation products such as conjugated dienes, volatile hydrocarbonates could shed some light upon the dimension of the pro/antioxidant balance in the development of periodontal impairment.